Versatile, low-cost ophthalmic wet lab device to improve diagnostic and surgical eye training - Mardianto, Umar; Victor, Andi Arus; Yusuf, Prasandhya Astagiri; Juniantito, Vetnizah; Kekalih, Aria; Rahayu, Tri; Bustamam, Alhadi; Edwar, Lukman (Faculty of Medicine Universitas Indonesia, 2026)
Ophthalmologists rely on wet lab training for both diagnostic procedures and surgical techniques. Existing wet lab devices are limited to surgical training and lack functionality for performing required perioperative diagnostic examinations. This study aimed to develop an affordable, easily manufactured eye holder to enhance ophthalmology training for wet lab simulations. A three-dimensional (3D)-printed animal eye holder was designed in 3D with a funnel-shaped structure resembling an orbital eye socket. The design was optimized for optimal wet lab activities. The animal eye holder device demonstrated potential use for ultrasound biometry, handheld keratometry, tonometry, and ophthalmological surgical training. These activities can be performed effectively after the animals’ eyes are stabilized inside the holder in flat and inclined positions. This innovative animal eye holder is the first designed to provide flexible diagnostic practice and surgical training, especially during wet lab activities.